To find the equation that describes the sequence \(1, 5, 25, \ldots\), we can analyze the terms.
- The first term (\(n = 1\)) is \(1\).
- The second term (\(n = 2\)) is \(5\).
- The third term (\(n = 3\)) is \(25\).
We can notice that these terms can also be expressed as powers of \(5\):
- \(a_1 = 5^0 = 1\)
- \(a_2 = 5^1 = 5\)
- \(a_3 = 5^2 = 25\)
In general, it appears that the \(n\)-th term of the sequence can be expressed as: \[ a_n = 5^{n - 1} \]
So the final equation for the \(n\)-th term of the sequence is: \[ a_n = 5^{n - 1} \]